THE EFFECT OF AUTHENTIC MATERIALS ON VOCABULARY ACQUISITION IN ENGLISH CLASSES - Juraev , Islombek (Bulletin of scientific research TUES, 2026)
Vocabulary acquisition remains a central component of second language development and plays a decisive role in learners’ communicative competence. Despite extensive research on lexical instruction, questions persist regarding the most effective pedagogical tools for facilitating long-term vocabulary retention and contextual usage. Authentic materials—texts, audio, and visual resources originally produced for native speakers—have been increasingly integrated into English language classrooms as a means of enhancing learner engagement and contextual exposure. However, empirical evidence concerning their measurable impact on vocabulary acquisition remains insufficient in certain educational contexts. The present quasi-experimental study investigates the effect of authentic materials on vocabulary acquisition among intermediate-level English learners. Over a twelve-week instructional period, two groups of university students were exposed to different instructional approaches: one group received vocabulary instruction through textbook-based materials, while the experimental group engaged with carefully selected authentic resources, including newspaper articles, podcasts, and video interviews. Vocabulary knowledge was measured through pre-tests, post-tests, delayed retention tests, and qualitative learner reflections. Statistical analysis revealed significant improvement in the experimental group not only in immediate vocabulary gain but also in long-term retention and contextual application. The findings suggest that authentic materials facilitate deeper lexical processing, enhance semantic network development, and promote meaningful engagement with language input. The study contributes to pedagogical theory by providing empirical support for integrating authentic resources into vocabulary instruction within English as a Foreign Language (EFL) contexts.